토양 방선균 Streptomyces cinereoruber 균주 배양여액의 살초특성 - 최정섭(Jung Sup Choi); 김영숙(Young Sook Kim); 장경수(Kyoung Soo Jang); 임희경(He Kyoung Lim); 조광민(Kwang Min Cho); 박기웅(Kee Woong Park) (Weed & turfgrass science, 2022)
Due to the toxicity issues of synthetic herbicides, microbe-derived herbicides are currently emerging as attractive alternatives to agriculture. This study was conducted to investigate herbicidal characteristics of a streptomyces candidate. According to the 16S rRNA sequence comparison, KRA18-316 was identified as Streptomyces cinereoruber. When the broth filtrate of KRA18-316 was applied to Digitaria ciliaris and Abutilon avicennae in the Petri-dish experiment, the seed germination rates was not affected but root growth was significantly reduced. Postapplications of the KRA18-316 broth extracts was highly effective to the grass species such as Sorghum bicolor or D. ciliaris with 70-100% of control value, compared with broadleaf species with 40-70% of control value. S. cinereoruber may be a novel Streptomyces candidate for bioherbicide and can be developed as a contact herbicide to control grass weed species. KCI Citation Count: 0